ChemInform Abstract: Recent Developments in the Chiral Broensted Acid‐Catalyzed Allylboration Reaction with Polyfunctionalized Substrates. Issue 42 (September 2016) - Barrio, Pablo; Rodriguez, Elsa; Fustero, Santos
Abstract: Review: [37 refs.